Beneficial properties of Garcinia atroviridis griff. fruit and leaf aqueous extract in experimental atherossclerosis in rabbits - Isemaail, Nursakinah (2012)
Numerous plants were proven beneficial in preventing atherosclerosis. The plant Garcinia atroviridis, locally known as asam gelugur had been traditionally utilized for various medicinal purpose. The present study aimed to evaluate the potential benefit of G.atroviridis fruit and leaf aqueous extracts supplementation by assessing the lipid profiles, antioxidant and liver enzymes, and atherosclerosis development in atherosclerosis-induced rabbits. The fruit and leaf samples were collected fresh from parts of Kedah, Malaysia; cut into pieces, dried in an oven at 30°C for 2 days and powdered. Then, 100 g of fruits and leaves powder were soaked separately in 1000 ml distilled water, incubated in water bath at three temperatures and time settings (40°C for 12 hours; 60°C for 6 hours; lOO°C for 15 min) to optimize their antioxidant ability, filtered and spray dried. The antioxidant activity was evaluated using the 1, I-diphenyl-2- picrylhydrazyl (DPPH) scavenging and Ferric Reducing Antioxidant Power assay. Total phenolic content was measured by the Folin Ciocalteu method. The leaf extract (89.2%) comparable to synthetic antioxidant butylated hydroxy toluene (94.6%). The fruit and leaf extracts prepared at 60°C for 6 hours, and 100°C for 15 min, respectively offered the highest antioxidant activity and phenolic contents, and therefore were supplemented to the rabbits. The extracts were force-fed once daily for 12 weeks at the dose of 50 mg/kg (F50), 100 mg/kg (FI00) and 200 mg/kg (F200) for fruits; and 5 mg/kg (L5), 55 mg/kg (L55) and 105 mg/kg (LI05) for leaves. Three control groups were excluded from the extract supplementation. All rabbits were fed a 0.5% cholesterol enriched diet, except the normal control group. The simvastatin control group was prescribed 10 mg/kg simvastatin while the positive control group was without any supplementation. Blood samples were collected via marginal ear vein at the beginning and every 4 weeks. As the experiment end, the leaf (LI05) and fruit (F50, FI00 and F200) supplementations significantly (p<0.05) retained the enzyme superoxide dismutase at its initial level. All extracts supplementations significantly reduced (p<0.05) lipid profiles (total cholesterol, triglycerides and low density lipoprotein) and liver enzymes (alkaline phosphatase, gamma-glutamyl transpeptidase and aspartate aminotransfarase). Both extracts had effectively prevented liver damage and atherosclerotic plaque formation with at least 25% lower atherogenic index than the positive control group. Hence, this study signifies the potential benefits of G. otroviridis fruit and leaf extracts as antioxidants, hypocholesterolemic, hepatoprotective, and anti-atherosclerotic agents.